Vibrational structure of free and hydrogen bonded complexes of isoniazid: FT-IR, FT-Raman and DFT study - Akalın, Elif; AKYÜZ, SEVİM (Elsevier, 2007)
The combined experimental and theoretical study on molecular vibrations of isoniazid (INH) were reported by using density functional (DFT) method to determine the geometric and vibrational characteristics of INH with the B3LYP/6-31++G(d,p) basis set. Anharmonic corrections to the wavenumbers were done and the results led to a good overall agreement with the observed wavenumbers. A complete assignment of the fundamentals was proposed based on the total energy distribution (TED) calculation. The calculated harmonic wavenumbers were also scaled by a single scaling factor (0.974) however the calculated anharmonic wavenumbers were shown to be superior to the scaled wavenumbers in being much closer to the observed wavenumbers in amount. To investigate the hydrogen bonding interactions of INH, hydrogen bonded complexes of the molecule (H2OINH) were studied, again using DFT method with B3LYP/6-31++G(d,p) basis set both at harmonic and anharmonic levels. To see the solvent effect on the free INH molecule, another calculation was done using DFT/B3LYP/6-31++G(d,p) in connection with PCM (Polarizable Continuum Model – water chosen as the solvent).
Keywords: Isoniazid; Isonicotinic acid hydrazide; Density functional theory; Infrared and Raman spectra; Water complex; Antituberculosis drug